2015
DOI: 10.2174/1570159x14666151109111054
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in the therapy of neurological diseases. Where is it going?

Abstract: Selenium ( 34 Se), an antioxidant trace element, is an important regulator of brain function. These beneficial properties that Se possesses are attributed to its ability to be incorporated into selenoproteins as an amino acid. Several selenoproteins are expressed in the brain, in which some of them, e.g. glutathione peroxidases (GPxs), thioredoxin reductases (TrxRs) or selenoprotein P (SelP), are strongly involved in antioxidant defence and in maintaining intercellular reducing conditions. Since increased oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 156 publications
0
12
0
1
Order By: Relevance
“…The antioxidant activity of selenoproteins in the CNS is well recognized, and deficiency of Se elicits brain injury (Fang et al 2013). In addition to the role of Se as an essential component of the antioxidant system in the brain, studies have further demonstrated that Se can assuage oxidative stress in the brain through the regulation of Ca 2+ channels, mitochondrial biogenesis, and apoptosis (Steinbrenner and Sies 2013;Dominiak et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity of selenoproteins in the CNS is well recognized, and deficiency of Se elicits brain injury (Fang et al 2013). In addition to the role of Se as an essential component of the antioxidant system in the brain, studies have further demonstrated that Se can assuage oxidative stress in the brain through the regulation of Ca 2+ channels, mitochondrial biogenesis, and apoptosis (Steinbrenner and Sies 2013;Dominiak et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Se administration was found to markedly decrease the levels of inflammatory cytokines such as TNF-α and interleukin-1β in the prefrontal cortex and hippocampus 13. Furthermore, animal model histopathologic analyses have suggested that sodium selenite treatment reduces perineuronal and pericapillary edema and increases neuronal density in the prefrontal cortex and the hippocampus 18. Se-induced prevention of mitochondrial dysfunction may also significantly contribute to reduced ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…22 Evidence from the literature indicates that the major beneficial effect of Se is related to its antioxidant nature and its anti-inflammatory role in the GPx system. 18,23 Accumulated evidence from clinical trials involving patients with burns, sepsis, traumatic brain injury, adult respiratory distress syndrome, neurodegenerative diseases, cancer, and pancreatitis suggests that early Se supplementation may significantly affect patient outcomes. Moreover, an increased chance of regaining consciousness after cardiac arrest was reported with early Se administration.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 In mammals, lack of Se intake has been linked to health disorders including reduced antioxidant defense functioning, which in turn can result in increased incidences of cardiovascular and neurodegenerative diseases as well as various inflammatory syndromes. 11,12 In addition, Se deficiency has also been linked to reduced immune functioning, hypothyroidism and increased cancer susceptibility. 12 Indeed, optimum Se intake (supplementation) has been shown to have a potential preventative effect regarding certain cancers.…”
Section: Introductionmentioning
confidence: 99%